SOSIALISASI PENGGUNAAN APLIKASI SURAT DIGITAL DI SMK BINA JAYA PALEMBANG - Mohammad Fadhli; Asriyadi Asriyadi; Lindawati Lindawati; Salwa Kamila; M. Redho Ali Said (LPPM Universitas Abdurrab, 2023)
There are several problems if an institution issues a letter conventionally. A conventional letter uses signatures and stamps that are easily forged. Conventional systems are also considered inefficient in terms of time and cost. Bina Jaya Palembang Vocational School is an educational institution in Palembang that conducts correspondence as one of its administrative activities. This community service program aims to socialize digital mail applications that can help increase the efficiency of correspondence activities and prevent the forgery of letters. This activity was carried out by disseminating a research result in a digital letter application. The first stage of this socialization activity is the preparation stage, followed by the initial survey, the implementation of the service, and the reporting stage. This socialization activity leads to the conclusion that the participants can understand the importance of using this digital mail application and its procedures.